Nansen and the Fram (plus 7 other stories) - Allison, I (The Royal Society of Tasmania, 2018)
The last two frontiers on Earth, the Antarctic and the Arctic, are the stuff of heroes, heartache, courage, mystery, misery, endurance and loss. All these and more are captured in the pages of Poles Apart: Fascination, Fame and Folly. This wonderful book lays out, in a series of snapshots, mankinds incredible persistent battle in firstly taming and secondly understanding our amazing icy wilderness.